Chickpea (Cicer arietinum L.) responds to inoculation with Azotobacter vineladii and Burkholderia cepacia at reduced dose of nitrogen fertilizer - Sánchez-Yáñez, Juan Manuel (2014)
Chickpea (Cicer arietinum L.) crop demands nitrogen fertilizer (NF) applied in excess caused lost soil fertility and environmental pollution. An alternative for solving this problem are: to reduce and to optimize NF in chickpea using inoculants based on plant growth promoting bacteria (PGPB) genus. Thus, the aim of this study was to analyze the response of chickpea to inoculation with Azotobacter vinelandii and Burkholderia cepacia at 50% reduced dose of NF. These PGPB were inoculated chickpea under an experimental design of randomized blocks. The response variables to measure the effect of PGPB on the legume were: the percent of germination, shoot and root phenotyping: plant height, root length and biomass: fresh and dry weight of shoot and root. Experimental data were analyzed by ANOVA and Tukey test. Results showed that a positive respond of chickpea to both PGPB on its germination as well as at seeding and flowering where chickpea had 0.82g total dry weight (TDW) of this value was statistically different and significant compared to chickpea treated by NF 100% not inoculated used as relative control (RC) with 0.71g TDW. This data suggests that chickpea optimized NF reduced dose by synergistic interaction of both genera PGPB in its root system. Which could to avoid in part soil lost fertility and environmental pollution for applying NF in excess.